Elymbos: A Karpathian village: The structure of an "Archaic" society - Capetanakis, Sissi (The Greek Review of Social Research, 1981)
Elymbos, situated on the Island of Karpathos. is a deeply stratified village community, structured around three complementary dichotomies: the first, between men and women, is revealed in the ex istence of two lines of descent: the one paternal/masculine, the other maternal/feminine: the second dichotomy is founded on relative age. introducing discrimination between the oldest and youngest of both sexes; the third is between two socio-professional groups: agri culturists and shepherds. This system constitutes the reference model. Mass emigration is causing the progressive depopulation of the village. Yet. even if the periodical return of the emigrants has led to the upheaval of traditional social organization, the restructuring of society which reveals a conflict between two different sets of values: that of the tradiotional system and that of the outside world, is superimposed on the reference model, though it has been drained of its functional substance.